Gender impact on consumer perception of packaging colour based on neuromarketing algorithms - Natalia N. Kalkova (Управленец, 2024)
The introduction of neuromarketing tools has created additional opportunities for deciphering consumer behaviour through studying neurophysiological responses to marketing incentives. The article aims to examine the effect of packaging colour on consumer behaviour when choosing cheese products. The principles of sensory marketing constitute the methodological framework of the study. It applies neurophysiological methods to investigate consumer reactions during visual examination of the packaging colour. Electroencephalogram (EEG) recordings and emotional responses identified by the Facial Action Coding System are used as empirical evidence. Vectors of emotional response were assessed using EmoDetect software. The research results show that the cheese packaging colour affects consumer choice, and its perception varies by gender and product group. According to EEG data analysis, the most intense emotional response in women was triggered by red cheese packaging, while blue packaging produced the least intense reaction. In men, it was black and white colours of boxes that induced the strongest and the weakest reaction, respectively. In women, a positive emotional response was recorded during visual examination of white and red cheese packaging, in men – of black ones. The most intense negative reactions were associated with blue and white packaging in women and men, respectively. Our study confirms that there are differences in emotional perception of the packaging colour between women and men, which should be considered by manufacturers to capture and keep consumer attention when marketing their products.